PENGARUH KESADARAN WAJIB PAJAK DAN PENGETAHUAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB) DI KECAMATAN BATHIN SOLAPAN KOTA DURI, RIAU - Maharaja, Elvin Febrianto; Elim, Inggriani; Suwetja, I Gede (Universitas Sam Ratulangi, 2021)
Tax is an obligation that must be paid by individuals to the state concerned in the law without getting direct payment, used for financing and state development and for national peace. This study aims to examine the effect of taxpayer awareness, and taxpayer knowledge, on taxpayer compliance in paying land and building taxes. The researcher used quantitative descriptive method. The data obtained in the form of primary data using a questionnaire. The statistical technique used is multiple regression analysis. The results show that partially; taxpayer awareness does not significantly affect taxpayer compliance, taxpayer knowledge significantly affects taxpayer compliance, Simultaneously; taxpayer awareness and taxpayer knowledge significantly affect taxpayer compliance.